Management, Global Edition - Robbins, Stephen P.; Coulter, Mary A. (Pearson International Content, 2024)
Management vividly illustrates effective management theories by incorporating the perspectives of real-life managers. Through examples, cases and hands-on exercises, you get to experience management in “action” and see how the concepts you’re reading about work in today’s dynamic business world.